Mechanisms of carrier transport in CdTe polycrystalline films - Sukach, A.V.; Tetyorkin, V.V.; Krolevec, N.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Cadmium telluride (CdTe) polycrystalline films grown on glass ceramic substrates by a modified close-spaced vapor transport technique have been investigated. The as-grown films have columnar structure with the average grain sizes about 10 μm. The in-plain direct current conductivity as a function of temperature and electric field has been investigated. The percolation conductivity is shown to be dominant at low temperatures (T < 250 K). At room temperature, the dominant transport mechanism is an activated process such as thermionic emission. The carrier transport across barriers is influenced by traps in the surface barrier regions. The non-annealed films exhibited stable electrical parameters and high photosensitivity during five-year storage under laboratory conditions.